University Students' Experiences and Reflections of Technology in Their Transition to Online Learning during the Global Pandemic - Therese Keane; Tanya Linden; Paul Hernandez-Martinez; Andreea Molnar (MDPI AG, 2022)
During the COVID-19 pandemic, technology has been used to a lesser or greater extent to facilitate learning and has become an instrumental part of ensuring continuity of education. Students had no choice but to engage in online learning during periods of lockdowns. The quick transition to online learning had the potential to significantly affect the student learning experience and, as a result, their attitudes to studying at university. In this study, we examined self-reported students' attitudes on their transition from face-to-face to online learning. Second-year students from Swinburne University of Technology in Melbourne, Australia, were invited to complete the questionnaire. Students reported a range of attitudes and experiences from very positive and enjoying discovering the new study mode to the very negative where motivation to study was lost and they were considering deferring or quitting their studies. Approximately half of the students discovered the benefits of both online and in-person education and expressed a preference for learning in a blended learning environment. The study results demonstrate the importance of digital technologies that provide flexible and agile educational opportunities with many students being open to new learning experiences despite missing the traditional approaches to education. The results of this study could inform further educational interventions when there is a need to move to online learning with little notice.